Analisis Kesulitan Dan Solusi Guru Dalam Menyusun RPP Kurikulum 2013 Di SD Swasta PAB 12 Sampali - Fadillah Putri Adeana; Zahra Azzura Zaffa; Siti Amalia Daulay; Aulia Rahman; Safran Safran (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2024)
This article analyzes teachers' difficulties and solutions in compiling the 2013 Curriculum RPP at PAB 12 Sampali Private Elementary School with a study formulation, namely firstly the teacher's difficulties in compiling the 2013 Curriculum RPP, secondly the elements that created challenges for the teacher in creating the 2013 Curriculum RPP, and thirdly, the solution that the teacher used in creating the 2013 Curriculum RPP. The RPP for the 2013 Curriculum. In order to get to the bottom of things, this study used descriptive qualitative approaches using data gathering tools including interviews, observations, and recording. Teachers had a hard time with several aspects of the 2013 Curriculum RPP preparation, according to the study. Among these challenges were coming up with indicators of competence accomplishment, deciding on learning methods and media, assembling learning stages, and constructing assessment instruments. Second, the factors that cause teachers' difficulties in preparing RPP for the 2013 Curriculum are that the components in the RPP for the 2013 Curriculum are considered complicated by teachers, teachers have not received training in preparing RPP for the 2013 Curriculum and teachers do not have time to prepare RPP for the 2013 Curriculum. Third, teacher solutions in overcoming difficulties In preparing the 2013 Curriculum RPP, there are three teacher solutions, namely using RPP from other teachers or RPP from the internet, using components that are already in the teacher's book and conducting discussions and sharing with other teachers.